Immune microenvironment heterogeneity characterizes biologically distinct KRASmut/SPOPmut and KRASmut/PIK3CAmut mesonephric-like adenocarcinoma subtypes revealed by integrated whole-exome and transcriptomic profiling - Zeng, Jing; Li, Qingli; Li, Kemin; Yang, Lu; Xu, Lian; Wang, Wei; Yang, Kaixuan; Wei, Qingbo; Wang, Jin; Zhu, Changbin; Yin, Rutie (Frontiers in Immunology, 2025)
ObjectiveThis study aims to uncover the molecular biology and immune microenvironment of gynecological mesonephric-like adenocarcinoma (MLA).MethodsTo determine the comprehensive characteristics of MLA, 17 patients with MLA were retrospectively enrolled in this study. Whole-exome sequencing and mRNA sequencing were performed to explore the molecular features. The biological differences between MLAs and epithelial-initiated gynecologic tumors reported in The Cancer Genome Atlas database were also analyzed.ResultsKRAS mutations (82.4%) were considered the driving mechanism and were co-mutated with PIK3CA (47.1%) and SPOP (23.5%), but their functions were mutually exclusive. In addition, pathways and genes associated with kidney development were upregulated in MLA patients. Compared with adjacent tissues and common gynecological tumors in The Cancer Genome Atlas, Th2 signature and resting mast cells account for the majority in MLAs, rendering an immunosuppressive TME. Particularly, the expression levels of IFNG, IFN6, and IFN1 KRAS_SPOP group, significantly lower than the rates found in KRAS_PIK3CA group. KRAS_SPOP mutant MLAs, exhibited reduced immune infiltration in their tumor microenvironment.ConclusionThis is the first study to demonstrate the comprehensive molecular characteristics of MLA and detect biologically distinct subtypes of KRASmut/SPOPmut and KRASmut/PIK3CAmut MLAs.